2019
DOI: 10.1080/02705060.2018.1542353
|View full text |Cite
|
Sign up to set email alerts
|

Spatial prediction of stream physicochemical parameters for the Napo River Basin, Ecuador

Abstract: Major threats to freshwater ecosystems in the Andean-Amazon region include agriculture, point and nonpoint source pollution, hydroelectric dams, oil extraction, mining and road building, yet little is known about the baseline values and current state of rivers and streams, or how expanding urban, industrial and agricultural activities could affect and change these freshwater ecosystems and their diversity. Therefore, there is a need to understand physicochemical parameters at the basin scale in many large rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The impact of the latter type of stressors is very severe and interrupts the dynamics and ecological functions that normally are given by the site-specific conditions, the seasonal fluctuations of the physical-chemical variables, or the temporal patterns of rainfall, which determine the composition of aquatic invertebrate communities. Instead, biological communities decline dramatically in terms of abundance and diversity, and, in some cases, they even disappear from the impacted systems [9,54,61]. Comparable findings are reported in several similar studies in other tropical regions (e.g., [87][88][89][90][91]).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The impact of the latter type of stressors is very severe and interrupts the dynamics and ecological functions that normally are given by the site-specific conditions, the seasonal fluctuations of the physical-chemical variables, or the temporal patterns of rainfall, which determine the composition of aquatic invertebrate communities. Instead, biological communities decline dramatically in terms of abundance and diversity, and, in some cases, they even disappear from the impacted systems [9,54,61]. Comparable findings are reported in several similar studies in other tropical regions (e.g., [87][88][89][90][91]).…”
Section: Discussionsupporting
confidence: 66%
“…Both the CRB and ARB discharge the water into the Napo River within the Ecuadorian territory before joining the Amazon River. The highland rivers from the Napo basin (such as Coca, Tiputini, Yasuní, Aguarico) are known as "aguas blancas" (white waters) [54]. The whitewater systems originate in the Andean snowmelts and high altitude paramo grasslands at elevations over 4000 m, and have a muddy colour caused by drainage carrying heavy sediment loads from eroding uplands [57].…”
Section: Study Area and Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we estimated the deviations from human development by calculating the absolute difference between observed values and references values. These reference values were obtained from Alexiades et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study of the Salado Estuary found bioaccumulation of Hg in mussels and poor quality parameters such as low dissolved oxygen (DO) to be indicative of limited biodiversity and diminished body sizes among local fish populations [56]. Nevertheless, it is important to recognize that fluctuations in pH, temperature, DO, and other parameters are also informed by natural and seasonal variation [57]. For example, in a study of the Napo River Basin, these parameters varied both spatially and temporally as a result of geographical and seasonal changes [57].…”
Section: Artisanal and Small-scale Gold Mining (Asgm) Pollution Factorsmentioning
confidence: 99%